The less prominent types in figurative language by motionless in white’s reincarnate (2014) - Khaira Fadhlika Ramadhani; Leni Marlina; G. Nancy Elizabeth (Researcher and Lecturer Society, 2026)
This study aims to identify and analyze the less prominent types of figurative language in three selected songs from Motionless in White’s Reincarnate (2014) album. Using a qualitative research design, the study explores how personification, hyperbole, simile, and onomatopoeia function to express emotion, intensity, and atmosphere in the lyrics. The data were collected from the songs Reincarnate, Puppets 3 (The Grand Finale), and Break the Cycle. The analysis applies theories from Abrams and Harpham (2015), Perrine (1982), and Leech (1981) to classify and interpret figurative expressions. The results show that while metaphor remains the dominant device in the album, other figures play crucial roles in enriching the lyrical meaning and enhancing emotional depth. Personification humanizes abstract concepts, hyperbole amplifies emotional power, simile clarifies abstract imagery, and onomatopoeia strengthens the auditory texture of the songs. The study concludes that these less prominent types serve as complementary linguistic tools that reinforce the album’s dark yet poetic tone.